Usability Studies: Sepeda Patroli Di Area Kampus: PATROL BICYCLES IN CAMPUS AREAS - William Santoso; Hairunnas - (Jurnal Desain Produk Nasional, 2026)
Patrol activities are an important element in maintaining the security and safety of the campus environment. However, at Universitas Surabaya (UBAYA) campus, security (SATPAM) patrol activities are still dominated by walking and the use of gasoline-powered motor vehicles, which have limitations in range, efficiency, and environmental impact. This study addresses the theme of usability studies in designing an electric bike as a campus patrol vehicle, with the need for a more adaptive, ergonomic, and sustainable patrol facility. The aim of this research is to formulate criteria and design decisions for an electric bike that align with the operational needs of UBAYA's SATPAM and serve as the foundation for the final design project. The research method used is qualitative through field observations, in-depth interviews with the head of UBAYA's SATPAM, literature studies, and trials of electric bike use on campus. The research process focused on the analysis of frame ergonomics, drive system, bicycle size, and patrol-supporting components in accordance with electric bicycle regulations in Indonesia. The results of the study indicate that an electric bicycle with an ergonomic frame in an upright sitting position, a hub motor drive system, and adjustments in wheel and handle sizes is more suitable for low-speed, repetitive campus patrol patterns. The novelty of this research lies in the formulation of an electric bicycle design that is specifically contextualized for the needs of campus patrols in Indonesia, using a human-centered design approach and environmental sustainability principles.